Study of Ascorbic Acid as Iron(III) Reducing Agent for Spectrophotometric Iron Speciation - Antesar Elmagirbi; Hermin Sulistyarti; Atikah Atikah (The Journal of Pure and Applied Chemistry Research, 2012)
The study of ascorbic acid as a reducing agent for iron(III) has been investigated in order to obtain an alternative carcinogenic reducing agent, hydroxylamine, used in spectrophotometric standard method based on the formation of a red-orange complex of Fe(II)-o-phenanthroline. The study was optimised with regards to ascorbic acid concentration as well as pH solution. The results showed that ascorbic acid showed maximum capacity as reducing agent of iron(III) under concentration of 4.46.10-4 M and pH solution of 1-4.Under these conditions, ascorbic acid reduced iron(III) proportionally and performed similarly to that of hydroxylamine.  The method gave result to linear calibration over the range of 0.2-2 mg/L withhigh accuracy of 97 % and relative standard deviation of less than 2 %. This method was successfully applied to assay iron speciation in water samples.